Mulheres e roupas : as feministas da Federação Brasileira pelo Progresso Feminino (1922-1936) - Pires, Herculanum Ghirello (2016)
The relationship of women with fashion is examined in this work through the feminists who acted in the Brazilian Federation for Women's Progress (FBPF). Created in 1922 in Rio de Janeiro, by Bertha Lutz. (1894 - 1976) and with the active participation of women in the elite segment. The FBPF played a key role in the struggle for social and political direct segments of the female laying the foundation of Brazilian feminism, in particular, to education and to vote. In this study, we consider that in the 1922 period to 1936, after winning the right to vote in 1932, Bertha Lutz was elected deputy to the wave of federal deputy in 1934, and in 1936 winning the vacant due to bankruptcy of the owner, these meetings of these women who joined the struggle and claims were permeated fashion. Meetings and meetings promoted by feminists; in places where discussions took place; the clothes worn by them to attend the events in this study were designed as fashionable vehicles. Capture in written and visual documents of the National Archives collections - with the help of the press, in particular in the paper magazine Fon-Fon! and Revista da Semana - fashion produced and disseminated among the feminists and women is the goal of this work. The hypothesis that guides the narrative is that the social, political and cultural transformations observed in the spaces of Rio's capital found in feminist a foothold, something like a 'civilizing process', to instill new values, behaviors and attitudes of women tuning -as with social and political rights and with fashion